Effects of Occupational Exposure on Lung Function Tests in Old Process Plant Units workers, North Oil Company, Iraq - Muhammad, Abdulwahed H.; Helal, Ahmad S. (Journal of Petroleum Research and Studies, 2021)
Occupational exposure to petroleum vapors has been shown to affect functioning of different systems of the body. The present study was taken up to assess the Pulmonary Function Tests. Method: A total of 356 male old process plant units’ workers in north oil company, Kirkuk, Iraq, were assessed for lung function status. Respiratory function test was according to the American Thoracic Society (ATS) recommendations, Questionnaire performed and respiratory functions viz. (FVC, FEV1, FEV1/FVC% and PEF) were recorded by a portable electronic spirometer. Results: There was a statistically significant decrease in FEV1, FVC, and PEF in this study of exposured state compared to the normal state which was normal. FEV1/FVC% ratio was within normal limit. Conclusion: Most findings point towards adverse effects of petroleum vapors on lung function, mainly on lower airways with restrictive pattern of disease.